2022
DOI: 10.1519/jsc.0000000000004307
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Responses to External Cues Are Specific to Both the Type of Cue and Type of Exercise in Adolescent Athletes

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…The reason for this could potentially be explained by the rate of cognitive development in children and adolescents whose frontal lobes continue to mature as they grow [ 37 ]. Whilst concepts such as the constrained action hypothesis might serve as an effective model for motor performance and learning in adults, an alternative approach could be more appropriate in certain (perhaps naïve) youth groups due to the aforementioned factors, though evidence to the contrary does exist [ 38 , 39 ]. In relation to the current study, it is possible that this process was observed at work with the young participants at the testing centres potentially less receptive to the coaching cues provided by the investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this could potentially be explained by the rate of cognitive development in children and adolescents whose frontal lobes continue to mature as they grow [ 37 ]. Whilst concepts such as the constrained action hypothesis might serve as an effective model for motor performance and learning in adults, an alternative approach could be more appropriate in certain (perhaps naïve) youth groups due to the aforementioned factors, though evidence to the contrary does exist [ 38 , 39 ]. In relation to the current study, it is possible that this process was observed at work with the young participants at the testing centres potentially less receptive to the coaching cues provided by the investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whilst adults have been shown to focus on relevant cues only, children focus on both relevant and irrelevant cues and this could potentially impact on the level of attention they devote to a specific instruction [ 40 ]. On the contrary, it is important to consider that if a young individual achieves a sufficient volume and quality of training, it is possible that they would no longer be considered to be a naïve perceiver and so may respond more readily to ADCs or ECs when provided by a coach [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The range of loading rate (beats per minute), ankle dorsiflexion (over the edge of a step vs. 10 • incline vs. flat ground) and plantar flexion (partial vs. maximum height) requirements reported in research may have contributed to the inconsistency seen clinically [10]. Specific instructions and cues have been a key consideration in contemporary research and clinical settings to help standardise practice [11]. Performance and technique cues during the SLHR test may alter the number of repetitions to failure performed and potentially provide a more robust indication of an individual's capacity when screening athletes [12,13].…”
Section: Introductionmentioning
confidence: 99%